THE CHANGE OF EMOTION AND THE HUMAN ROLE IN THE PRESENT - Osman Emin; Havva Saban (Vision International Scientific Journal, 2019)
By understanding our existing emotions, we recognize the changes in emotions, which emotions have effects on our body, in this way we not really exhaust our emotions. We must realize that human beings have a great share in their emotions and reactions to emotions. According to the studies, nowadays, the ability to manage emotions, to benefit from them effectively, and to have a balanced and harmonious life by understanding oneself and others, has revealed the concept of emotional intelligence. Studies have shown that individuals with high emotional intelligence are more adaptable and balanced and as a result emotional intelligence has emerged. Emotional awareness helps us know what we want and what we need. Being aware of our emotions can help us talk about feelings more clearly or resolve conflicts better, and avoid or move past difficult feelings more easily.
Keywords: Human, Emotion, Emotional changes